2020
DOI: 10.7717/peerj.9927
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of bacterial assemblages along the Loa River in the Atacama Desert, Chile

Abstract: The Loa River is the only perennial artery that crosses the Atacama Desert in northern Chile. It plays an important role in the ecological and economic development of the most water-stressed region, revealing the impact of the mining industry, which exacerbate regional water shortages for many organisms and ecological processes. Despite this, the river system has remained understudied. To our knowledge, this study provides the first effort to attempt to compare the microbial communities at spatial scale along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 88 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…In addition, multiple lake and ocean datasets are characterized by higher Eh7 for overlying water than sediment (Han et al, 2019;von Hoyningen-Huene et al, 2019;Vavourakis et al, 2019;Molina et al, 2021); most of these exhibit negative correlations with Z C , except for Honghu Lake (Han et al, 2019), which shows a relatively high Z C for water. A systematic difference in redox potential between water and sediment is not evident for river datasets (Cai et al, 2019;Zárate et al, 2020).…”
Section: Sediment and Soilmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, multiple lake and ocean datasets are characterized by higher Eh7 for overlying water than sediment (Han et al, 2019;von Hoyningen-Huene et al, 2019;Vavourakis et al, 2019;Molina et al, 2021); most of these exhibit negative correlations with Z C , except for Honghu Lake (Han et al, 2019), which shows a relatively high Z C for water. A systematic difference in redox potential between water and sediment is not evident for river datasets (Cai et al, 2019;Zárate et al, 2020).…”
Section: Sediment and Soilmentioning
confidence: 90%
“…The datasets with negative correlations represent marine (Sánchez-Soto Jiménez et al, 2018;Molina et al, 2021;Wu et al, 2021), coastal (Zhou et al, 2017), freshwater (Zárate et al, 2020;von Hoyningen-Huene et al, 2019), and hypersaline sediments (Vavourakis et al, 2019). The dataset with the most negative fitted slope is that for Daya Bay, China (Wu et al, 2021), where samples were collected from the surface, middle, and bottom of sediment cores.…”
Section: Sediment and Soilmentioning
confidence: 99%
“…This improves efficiency in transferring information, energy, and resources of microbial communities, regard to sediment nutrient conversion and pollutant biodegradation ( Santolini and Barabási, 2018 ; Philippot et al, 2021 ). One explanation for the high spatial connectivity and the selection of the microbe pool in the coastal area surrounding the OL may also be attributed to the Loa River, which acts as a true green/life corridor that runs across the hyper-arid core of the Atacama Desert also known as the dry limit for life on Earth, helping to establish specific networks ( Zárate et al, 2020 ). In this way, the input may support a distinct set of microbial processes that remain unstudied ( Fortunato et al, 2012 ; Fazi et al, 2020 ; Jroundi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation-based network analysis provides a good way to determine the potential interplays between microbes as well as their structuring and mediating ecological functions in various environments ( Chaffron et al, 2010 ; Banerjee et al, 2018 ; Felipe-Lucia et al, 2020 ), including the Mejillones Bay and Loa River ( Zárate et al, 2020 , 2021 ). Therefore, the results of the present study highlights important targets to better understand microbial responses to the bioavailability of TMs in low-oxygen sedimentary environments.…”
Section: Introductionmentioning
confidence: 99%
“…River microbiota is mostly studied in water or, less frequently, from sediment and very little is known about epilithon. Differences in microbial community structure in the two former habitats have been reported from the Yellow River estuary [ 28 ], the Ibrahim River, Lebanon [ 26 ], the sub-arctic Pasvik River, Norway [ 16 ], and from the Loa River, Atacama Desert, Chile [ 43 ], suggesting that type of river habitat is a key driver in community composition, regardless of climatic conditions. Our study demonstrated strong separation of water and epilithon communities in different Danube sections.…”
Section: Discussionmentioning
confidence: 99%